RELEVANCE OF WITHIN-GRADE CARTILAGE ASSESSMENT USING THE MOAKS SCORING INSTRUMENT AND CORRESPONDING QUANTITATIVE CARTILAGE THICKNESS LOSS: DATA FROM THE OAI FNIH BIOMARKERS CONSORTIUM STUDY - Roemer, Frank; Maschek, S.; Wisser, A.; Guermazi, A.; Hunter, D.; Wirth, W. (OSTEOARTHRITIS AND CARTILAGE, 2022)
Both semi-quantitative (SQ) MOAKS cartilage scores and quantitative (Q) cartilage thickness measurements are used as outcome measures in observational studies and interventional knee osteoarthritis (OA) trials. Both methods are considered complementary. SQ scoring by experts is considered less sensitive to change compared to Q approaches based on cartilage segmentation particularly regarding subtle wide-spread cartilage loss. On the other hand, change in focal defects commonly is not covered by Q approaches as these may be too subtle in the context of segmentation of an entire subregion. In order to increase sensitivity to change of SQ instruments in longitudinal observational studies or clinical DMOAD trials, so-called within-grade changes not fulfilling criteria of a full-grade change have been introduced in SQ assessment. While the validity of these changes has been shown, the association between longitudinal change of SQ-defined within-grade and full-grade changes and longitudinal Q cartilage loss has not been established. The Foundation for the National Institutes of Health (FNIH) OA Biomarkers Consortium is a nested case-control study based within the larger Osteoarthritis Initiative (OAI) study. One goal of this study was to determine the association between semiquantitative MRI biomarkers and knee OA progression over 48 months as defined by pre-determined medial radiographic, clinical or combined outcomes. Our aim was to study the association between full-grade only changes, within-grade only changes and full-grade plus within-grade change in MOAKS cartilage scores and concurrent change in quantitative cartilage thickness measurements over 24 months within the FNIH Biomarker Consortium study.<br
CRIS-Team WoS Importer:2022-04-22